Antitumor activity of intratracheal inhalation of temozolomide (TMZ) loaded into gold nanoparticles and/or liposomes against urethane-induced lung cancer in BALB/c mice - Mohamed A. Hamzawy; Amira M. Abo-youssef; Heba F. Salem; Sameh A. Mohammed (Taylor & Francis Group, 2017)
The current study aimed to develop gold nanoparticles (GNPs) and liposome-embedded gold nanoparticles (LGNPs) as drug carriers for temozolomide (TMZ) and investigate the possible therapeutic effects of intratracheal inhalation of nanoformulation of TMZ-loaded gold nanoparticles (TGNPs) and liposome-embedded TGNPs (LTGNPs) against urethane-induced lung cancer in BALB/c mice. Physicochemical characters and zeta potential studies for gold nanoparticles (GNPs) and liposome-embedded gold nanoparticles (LGNPs) were performed. The current study was conducted by inducing lung cancer chemically via repeated exposure to urethane in BALB/C mice. GNPs and LGNPs were exhibited in uniform spherical shape with adequate dispersion stability. GNPs and LGNPs showed no significant changes in comparison to control group with high safety profile, while TGNPs and LTGNPs succeed to improve all biochemical data and histological patterns. GNPs and LGNPs are promising drug carriers and succeeded in the delivery of small and efficient dose of temozolomide in treatment lung cancer. Antitumor activity was pronounced in animal-treated LTGNPs, these effects may be due to synergistic effects resulted from combination of temozolomide and gold nanoparticles and liposomes that may improve the drug distribution and penetration.